2023
DOI: 10.1097/rmr.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Spectroscopy of Lactate in Alzheimer Disease: A Comprehensive Review of Alzheimer Disease Pathology and the Role of Lactate

Abstract: Functional 1H magnetic resonance spectroscopy (fMRS) is a derivative of dynamic MRS imaging. This modality links physiologic metabolic responses with available activity and measures absolute or relative concentrations of various metabolites. According to clinical evidence, the mitochondrial glycolysis pathway is disrupted in many nervous system disorders, especially Alzheimer disease, resulting in the activation of anaerobic glycolysis and an increased rate of lactate production. Our study evaluates fMRS with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 152 publications
0
3
0
Order By: Relevance
“…Recent developments in brain imaging have increased the capacity to diagnose brain diseases. Functional 1 H magnetic resonance spectroscopy (fMRS) is becoming a powerful diagnostic tool for brain diseases [ 81 ]. It was reported that lactate evaluated with fMRS has the potential to be a new diagnostic and prognostic marker for AD [ 81 ].…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in brain imaging have increased the capacity to diagnose brain diseases. Functional 1 H magnetic resonance spectroscopy (fMRS) is becoming a powerful diagnostic tool for brain diseases [ 81 ]. It was reported that lactate evaluated with fMRS has the potential to be a new diagnostic and prognostic marker for AD [ 81 ].…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Functional 1 H magnetic resonance spectroscopy (fMRS) is becoming a powerful diagnostic tool for brain diseases [ 81 ]. It was reported that lactate evaluated with fMRS has the potential to be a new diagnostic and prognostic marker for AD [ 81 ]. As the mitochondrial glycolysis pathway is considered to be disrupted in many brain disorders, the activation of anaerobic glycolysis with increased lactate production must occur in the presence of various brain disorders.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…The MRS techniques enable spatiotemporal resolution of metabolites relevant to bioenergetics, and the characterisation of brain lactate dynamic responses through functional MRS (fMRS) is a promising tool to enable the direct assessment of mitochondrial homeostatic responses to neurometabolic stress [ 48 ]. Although measurement of lactate with MRS is challenging due to a low signal-to-noise ratio (SNR) in vivo, we opine that lactate has a key role that enables an integrated and precise approach for appreciating and understanding energy allocation and mitochondrial efficiency within the CNS that goes beyond oxygen and blood flow measurement [ 49 ]. Indeed, changes in brain lactate metabolism measured with MRS have already been used to characterise and monitor the response to pharmacological therapy in psychiatric conditions (see Section 4 ).…”
Section: Introductionmentioning
confidence: 99%